Supercontinuum generation in scintillator crystals - Vaida Marčiulionytė; Gintaras Tamošauskas; Matas Šutovas; Audrius Dubietis (Scientific Reports)
Abstract We present a comparative experimental study of supercontinuum generation in undoped scintillator crystals: bismuth germanate (BGO), yttrium orthosilicate (YSO), lutetium oxyorthosilicate (LSO), lutetium yttrium oxyorthosilicate (LYSO) and gadolinium gallium garnet (GGG), pumped by 180 fs fundamental harmonic pulses of an amplified Yb:KGW laser. In addition to these materials, experiments in yttrium aluminium garnet (YAG), potassium gadolinium tungstate (KGW) and lithium tantalate (LT) were performed under identical experimental settings (focusing geometry and sample thickness), which served for straightforward comparison of supercontinuum generation performances. The threshold and optimal (that produces optimized red-shifted spectral extent) pump pulse energies for supercontinuum generation were evaluated from detailed measurements of spectral broadening dynamics. The measured cut-off wavelengths at the short-wavelength side are in line with the general trend of blue-shifted spectral broadening on the bandgap of nonlinear material. All the nonlinear materials produced reasonable red-shifted spectral broadenings under conditions of optimal pump pulse energies, with the largest red-shift exceeding 2000 nm measured in GGG crystal. Our results revealed that GGG and BGO (which also had the lowest supercontinuum generation threshold) offer durable, optical damage-free performance at a laser repetition rate of 200 kHz, suggesting that these materials are good alternatives to YAG and KGW for low threshold, high average power supercontinuum generation in the near- and short-wave infrared spectral ranges. We also demonstrated that scintillating properties of bulk materials could be readily studied in the filamentation regime, via multiphoton excitation using near-infrared femtosecond laser pulses.